Prevalence and risk factors for aspirin resistance in older patients with cardiovascular disease. (12th October 2011) - Jian, Cao; Lin, Liu; Li, Fan
Abstract : Objectives: To evaluate the prevalence and risk factors for aspirin resistance in older patients with cardiovascular disease (CVD). Design: Cross-sectional analysis. Setting: General community. Participants: 454 patients aged 65 years or older with CVD. Measurements: The older patients received daily aspirin therapy (≥75 mg) over 1 month. Platelet aggregation was measured by light transmission aggregometry (LTA) and thrombelastography platelet mapping assay (TEG). Results: By LTA, 38 (8.4%) of older patients were found to be resistant to aspirin therapy; 166 (36.6%) patients were semiresponders. By TEG, 111 patients (24.4%) were aspirin-resistant. In the multivariate logistic regression analysis, Fasting serum glucose levels (odds ratio (OR)=1.211, 95% CI: 1.047 to 1.402, p=0.010), CD62P levels (OR=1.010, 95% CI: 1.002 to 1.019, p=0.019, p=0.019), the drugs of ACEIs/ARBs (OR=0.638, 95% CI: 0.414 to 0.983, p=0.042)and nitrates (OR=0.524, 95% CI: 0.309 to 0.890, p=0.017) were significantly associated with aspirin resistance or aspirin semiresponders. Conclusion: The prevalence of aspirin resistance or aspirin semiresponders in older patients with CVD was considerably higher in patients with higher fasting glucose levels, CD62P levels and in patients with changes in medication taken.